Larvicidal and pathological effects of green synthesized silver nanoparticles from Artemisia herba-alba against Spodoptera littoralis through feeding and contact application. Issue 1 (31st December 2022) - El-Ashmouny, Raghda S.; Rady, Magda H.; Merdan, Bouthaina A.; El-Sheikh, T. A. A.; Hassan, Rasha E.; El Gohary, El Gohary E
ABSTRACT: The development of effective and eco-friendly insecticides is a demand. Green nanoparticles synthesis is an important field in pest control strategy, which has cost effective and faster than physical and chemical methods. In this study, silver nanoparticles (AgNPs) were synthesized using Artemisia herba-alba plant extract to be tested against an important pest of non-edible plants such as cotton. UV-vis spectrophotometry, TEM, XRD and FTIR were used to confirm the biophysical characterization of AgNP formation, which appeared as spherical particles with size ranging from 9.68 to 36.7 nm. Feeding and contact application methods were used to evaluate the larvicidal activity of green-synthesized AgNPs against the cotton pest Spodoptera littoralis larvae. LC50 and LC90 values of synthesized AgNPs were calculated. After 5 days of treatment, the calculated LC50 of applied AgNPs by feeding application was 74.569 ml/ml (soln./ H2 O), whereas contact application recorded LC50 of 27.47 ml/ml after 30 h of treatment. Morphological and histopathological abnormalities after AgNPs treatment were detected as demelanization and mummified shape of larvae, the destruction of the cuticle layer, disintegration of gut epithelia and gonad deformation. Our results proved the success of green-synthesized NPs application against S. littoralis larva, which open new avenues in pest control.